Viscosity and viscometric properties of glycine in aqueous solutions of sodium thiosulfate pentahydrate (na2s2o3 .5h2o) at different temperatures (2014)
Flowing times of Glycine in aqueous solutions Sodium Thiosulfate Pentahydrate (0.01-2.0 mol kg-1) using an AMVn Anton Paar viscometer at temperatures of (283.15; 288.15; 293.15; 298.15; 303.15; 308.15, 313.15 and 318.15) K and 101.1 Kpa.From the data obtained, the absolute viscosity, viscosity B-coefficients, slope (dB/dT),the ΔBtr,adjustable parameters of the equation of Out and Los (BE, BS, K), activation parameters of viscous flow (ΔG°≠, ΔH°≠, ΔS°≠) were calculated , the values obtained for these parameters were discussed in terms of the interactions present in solution.